The Geologic Contribution to the Mountain lopes Instability and its effect on Rockfall Hazards. A Case Study to the Zintan Road, Jabal Nafusah, Libya Abdunaser - K.M , Abdunaser; Bergeg , Khaled; Swei, G, Swei, G; Saeed M (Sharwes Scientific Journal, 2023)
The paper is intended to address geological characteristics for risk evaluation of rockfall hazards attributable to the high cut in weathered rock that sometimes obstruct the passage of vehicles in the Zintan mountain road case study region and recommend mitigation steps to reduce these threats. The geological structure of the area, the composition of the rocks, the hydrologic conditions, and the steepness of the slopes all affect these materials’ strength and susceptibility to failure. The areas at the source of the falling rock have been identified. The evaluation of geological formation and its structures as rocky nits of slopes determined in this present study demonstrates that it is mostly comprised of friable rocks interbedded within hard rock such as dolomitic limestone. In addition, it contains a group of fractures and joints, which take different directions, with a slight dipping for the rock layers. Based on field investigation and a detailed study, the weathering and erosion effects of rocks have also been examined in all stratigraphic sequences that contribute to rockfalls. Sidi as Sid Formation which is composed of dolomitic limestone of Ain Tobe Member intrebedded with Yafran Marl Member is identified as the typical source areas of rockfalls. The results of this study indicate that the study area is at risk of rockfall and requires adequate preventive sures to reduce these risks. Finally suggestions and recommendations are made to predict rockfall and help provide optimal solutions.